Successful Utilization of the GLP-1 Receptor Agonist Semaglutide in Treating the Manifestations of Recalcitrant Celiac Disease - Bell, David S H; Jerkins, Terri (Archives of Clinical and Biomedical Research, 2025)
A refractory case of abdominal swelling (pseudoascites) due to celiac disease which did not respond to monotherapy with a gluten-free diet and for which treatment with traditional immunosuppressives was refused is described. Based on reports of the anti-inflammatory actions of the GLP-1 receptor agonist, semaglutide, weekly subcutaneous injections of semaglutide were added to the gluten-free diet with rapid and obvious success. Semaglutide and perhaps other GLP-1 receptor agonists should be considered for use as a largely safe anti-inflammatory drug in other autoimmunopathies and inflammatory states.